A novel method for measuring flotation recovery by means of 4D particle tracking velocimetry. (1st August 2018) - Sommer, A.-E.; Nikpay, M.; Heitkam, S.; Rudolph, M.; Eckert, K.
Highlights: 4D PTV was successfully applied to study bubble-particle attachment events. Polystyrene particles are promising as model particles for fine particle flotation. Limitations of existing collision probability models were revealed. Particles with a low inertia collided at the rear surface of the bubble. Abstract: This work focuses on analysing the collection process in flotation by means of a simultaneous time-resolved measurement of particle and bubble trajectories. We introduced a new method that determined the probability of collision and attachment using a 3D particle-tracking method with high temporal resolution (1000 fps) and spatial ( 0.03 mm/pixel) resolution in a dense particle flow ( 5000 particles/ml). A 4D particle image tracking device with three high-speed cameras recorded the three-phase flow in a rectangular bubble column (2 mm, bubble chain). Particles made of fluorescent polystyrene were employed so that particles appeared bright and bubbles dark on the captured images. An attachment occurred if the trajectory of a particle coincided with that of a bubble. The recovery was calculated based on the number of particles attached to a bubble compared to the total number of particles within a reference volume. With this method, the true flotation depending on the particle diameter ( 30 – 100 μ m) was investigated and the results compared with an existing model of the bubble-particle collection microprocess.